Economic Evaluation of Efficiency of Gas Pumping Units - Чучук, Ю. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Ukraine's gas transportation system requires modernization and restructuring, during which, it should be possible to change the energy source to drive the gas compressor units. This decision requires consideration of factors that affect the economic efficiency of the compressor station. It was developed complex index of the efficiency of gas pumping units, taking into account industry specifics of gas transportation by main pipelines.